Noble hardwoods network: Report of the third meeting, 13-16 June 1998, Sagadi, Estonia - Turok, J.; Jensen, J.; Palmberg-Lerche, C.; Rusanen, M.; Russel, K.; Vries, S. de; Lipman, E.; European Forest Genetic Resources Programme (1999)
The meeting focused on the further developments of strategies and methodologies for the genetic resources of Noble Hardwoods. Information on international developments in the area of forest genetics resources (FAO) and a summary of the activities of the other EUFORGEN Networks was also provided and discussed.